O paciente com infecção de vias aéreas superiores. Quando anestesiar? - Ganem, Eliana Marisa [UNESP]; Pinheiro Módolo, Norma Sueli [UNESP]; Machado Castiglia, Yara Marcondes [UNESP] (My University, 2003)
BACKGROUND AND OBJECTVES: Anesthesia in children with upper airway infection (UAI) is a major challenge for Anesthesiologists. This paper aimed at discussing why and when to induce anesthesia in UAI children. CONTENTS: Preoperative clinical history, factors contributing to peri and postoperative complications and the type of surgery and anesthetic technique favoring such complications are highlighted. CONCLUSIONS: The understanding of post-UAI respiratory tract changes, of the importance of accurately evaluating the severity of symptoms, of factors contributing to complications and of the best anesthetic technique will allow for the choice of patients at the lowest risk to develop perioperative complications.
Patient with upper airway infectious disease. When to induce anesthesia?
Keywords: Anesthesia, pediatric; Diseases: upper airway infection